Pengaruh Penerapan Model Pembelajaran Discovery Learning Menggunakan Media Power Point Terhadap Hasil Belajar Kognitif dan Keterampilan Proses IPA pada Siswa Kelas V Sekolah Dasar - Mustahiran; Irwan Koto; Puspa Djuwita (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to determine the effect of applying the Discover Learning learning model using power point on cognitive learning outcomes and science process skills in Class V. This type of research is quasi-experimental research or quasi-experimental. The design used in this study was a control group pre-testpost-test design. The subjects in this study were all fifth grade students at SD Negeri 2 Muara Kulam for the 2022/2023 academic year. Based on the results of the t-test, it was obtained that sig (2-tailed) = 0.047 < Î± = 0.05, then H0 was rejected and H1 was accepted. So it can be concluded that there is an effect of learning using the discovery learning model with PowerPoint class V students at SD Negeri 2 Muara Kulam on learning outcomes. Likewise with the results of sig (2-tailed) = 0.050 < Î± = 0.05 then H0 is rejected and H1 is accepted. So it can be concluded that there is an effect of learning using the discovery learning model with powerpoint fifth grade students at SD Negeri 2 Muara Kulam on science process skills.